Analysis of the Impact of Tiktok Content Creator on the Identification of F&B MSME Products - Rezi Muhamad Taufik Permana; Roro Arinda Reswanti Julian Pratama (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2022)
TikTok has played a significant role in the development of social media today. Where the role of TikTok has almost influenced all forms of perception for the audience. MSMEs, especially in food and beverage products. TikTok can be an appropriate promotional medium to introduce a strong brand position. This role becomes very important when there is a review or review from the Content Creator. For this reason, this study will examine how big the influence of TikTok Content Creator in introducing MSME food and beverage products. Using a quantitative method approach using a questionnaire instrument distributed through google form to find out the impact of TikTok Content Creator on product identification of F&B MSMEs. This approach is used to determine the condition of a phenomenon being discussed with the data analysis design.